PENERAPAN MANAJEMEN HIDUP SEHAT DALAM MENGATASI PENYEBARAN VIRUS COVID-19 DI DESA PADASUKA KECAMATAN BAROS KABUPATEN SERANG - Khaeruman; Adien Nurdiansyah; Iis Suryanah; Suflani; Ahmad Suherman; Fahad; Raden Irna Afriani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Activities carried out in this Community Service are through socialization activities on the application of healthy life management in overcoming the spread of the Covid-19 virus pandemic in the form of counseling on healthy life management management for residents of Padasuka Village, Serang Regency. Solutions to mobilize healthy living management habits with a healthy life management socialization system in order to overcome the spread of the Covid-19 virus, as well as the need for masks and hand sanitizers in order to ensure health and break the chain of the spread of Covid-19. The objectives of this service activity are 1) Increase understanding of the application of healthy living management in overcoming the spread of the Covid-19 Virus; 2) implementing healthy living management habits in overcoming the spread of the Covid-19 Virus. In the midst of conditions that will spread the Covid-19 virus, it is very necessary to socialize the application of healthy life management and prevention efforts which bring benefits 1) increasing understanding of the dangers of the Covid-19 virus, 2) increasing knowledge about how to prevent being infected with the Covid-19 virus , 3) increasing knowledge of how to wash hands properly, 4) increasing knowledge of how to maintain body resistance with healthy life management, 5) knowing how to take steps to implement a healthy lifestyle.